Vol 28 No 1 (2021) Pengaruh Self Assessment System Dan Penerapan E-Faktur Terhadap Ketepatan Waktu Pelaporan PPN Pengusaha Kena Pajak Pada Kantor Pelayanan Pajak Pratama Pondok Gede - Efa Nofitasari Efa Nofitasari; Bambang Tedja MR Bambang Tedja MR; Safrudin Safrudin (Cakrawala Akuntansi & Manajemen, 2021)
This study aims to determine the effect of the self assessment system and the application of e-invoices on the timeliness of reporting Value Added Tax (VAT) for taxable entrepreneurs at KPP Pratama Pondok Gede. The sample was taken by incidental sampling technique, with a total sample of 100 respondents. This research was conducted using primary data with a questionnaire by distributing it online. The data analysis technique used in this research is multiple linear regression, multiple linear correlation, and multiple linear determination. The analysis used in this study is a quantitative method using the SPSS program, with a significant value (α) of 5% with the Self Assessment System and the application of e-invoicing as the independent variable and the Timeliness of Reporting Value Added Tax (VAT) of Taxable Entrepreneurs as the dependent variable. Hypothesis testing with t-test shows that the Self Assessment System and e-Faktur implementation variables have a partially significant effect on Timeliness of Reporting Value added tax of Taxable Entrepreneurs with each significant value of 0.000 < 0.05 and 0.024 < 0.05. Meanwhile, simultaneously (together) the two variables, namely the Self Assessment System and the Implementation of e-Faktur, have a significant effect on the Timeliness of Reporting Value Added Taxes (VAT) for Taxable Entrepreneurs. The magnitude of the influence of the two variables, both the Self Assessment System and the Implementation of e-Invoices is 43.0% on the Timeliness of Reporting Value Added Taxes (VAT) for Taxable Entrepreneurs, while the remaining 57.0% are other variables outside of this study that affect the Timeliness of Tax Reporting. value added of the Taxable Entrepreneur.